Capsaicin’s Inhibition Effects on Biofilm Aerococcus Viridans (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Aerococci has colony shape with Streptococcus viridans, so that it is usually missdiagnosedbetween of them. It has high difficulty on its identification, because it is rarely to be found and resistant ofAntibiotic grup, called penicilin and vancomycin.Material and Method: This research used two kinds of samples, such as: fried food sold on the road and toothbrushobtained from ten respondens. Then, it needs inducing its biofilm and measuring by Tissue Culture Plate (TCP)methode and ELISA.Result: ANOVA one-way revealed that extract capsaicin has anti biofilm effect on 12.5% concentration withp=0,0000 (p
Keywords: UTI; antibiotic resistance; Bioterrorism; ELISA; traditional herbal medicine.